Design and implementation of Smart Relay Based Two-axis Sun Tracking System - Mahmood, Dr. jawad Radhi; Muhammed, Haider (Iraqi Journal for Electrical and Electronic Engineering, 2011)
Solar power is environment friendly power source, but it is characterized by being highly dependent on the irradiation level witch is function of the sun position in the sky. To overcome this situation and extract maximum power from the sun, the PV array must be kept nearly perpendicular to the sun during the daytime. In this paper, a smart relay based sun tracking system has been designed and implemented to keep the PV array perpendicular to the sun during the day hours.